Molecular characterisation of a novel cassava associated circular ssDNA virus - Dayaram, Anisha; Jäschke, Anja (Virus research, 2012)
The application of sequence non-speciﬁc rolling circle ampliﬁcation of circular single stranded (ss) DNA molecules to viral metagenomics has facilitated the discovery in various ecosystems of what is probably a diverse array of novel ssDNA viruses. Here we describe a putative novel ssDNA virus (at a genome level), cassava associated circular DNA virus (CasCV), isolated from cassava leaf samples infected with the fungi Collectotrichum and Plectosphaerella. CasCV has a circular ambisense genome and shares signiﬁcant genome similarities with Sclerotinia sclerotiorum hypovirulence-associated DNA virus 1 (SsHADV-1), Mosquito VEM virus SDBVL and Meles meles faecal virus (MmFV). The CasCV genome (2220 nt) has three large open reading frames. While it is probable that one of these encodes a capsid protein, the other two probably express a replication associated protein (Rep) following the removal of an intron such as that found in the Rep encoding genes of some geminiviruses. This Rep would contain four conserved rolling circle replication (RCR) related motifs that have previously been identiﬁed in geminivirus, circovirus and nanovirus Reps. Given both that the CasCV Rep and CP share 62.7% and 39.8% amino acid identity respectively with the Rep and CP of SsHADV-1, and that CasCV was discovered associated with cassava infecting fungi, we suggest that CasCV should be classiﬁed within the mycovirus taxonomic family. However, host range studies using infectious clones will be required to demonstrate the novel virus’ likely origin and actual host species.
Gesehen am 20.08.2018